2012
DOI: 10.1002/ejoc.201101434
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Directed Spin Labelling of Nucleic Acids

Abstract: The study of the structure and dynamics of the nucleic acids and their complexes with other biomolecules is the basis for understanding their functions. Electron paramagnetic resonance (EPR) spectroscopy is a biophysical technique that in recent years has been increasingly used to investigate nucleic acids. EPR studies require paramagnetic centre(s), usually nitroxide spin‐label(s) that are incorporated at specific sites in the nucleic acid by site‐directed spin labelling (SDSL). In the last few years, spin la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 137 publications
0
61
0
Order By: Relevance
“…Protocols for paramagnetic labeling of RNA oligonucleotides are also available (Ramos et al, 1999;Shelke & Sigurdsson, 2012;Su & Otting, 2010). Several methods have been developed to attach a paramagnetic tag to nucleic acids (Keyes & Bobst, 2002;Nguyen & Qin, 2012;Qin & Dieckmann, 2004;Shelke & Sigurdsson, 2012): these include replacing structural Mg 2+ with paramagnetic Mn 2+ (Bonneau & Legault, 2014;Kisseleva, Khvorova, Westhof, & Schiemann, 2005), attaching paramagnetic groups to 2 0 -amino modified nucleotides or 4-thiouridines (Piton et al, 2007;Qin, Feigon, & Hubbell, 2005), and the use of paramagnetic phosphoramidites during RNA synthesis (Wunderlich et al, 2013).…”
Section: Spin Labeling Of Protein-rna Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Protocols for paramagnetic labeling of RNA oligonucleotides are also available (Ramos et al, 1999;Shelke & Sigurdsson, 2012;Su & Otting, 2010). Several methods have been developed to attach a paramagnetic tag to nucleic acids (Keyes & Bobst, 2002;Nguyen & Qin, 2012;Qin & Dieckmann, 2004;Shelke & Sigurdsson, 2012): these include replacing structural Mg 2+ with paramagnetic Mn 2+ (Bonneau & Legault, 2014;Kisseleva, Khvorova, Westhof, & Schiemann, 2005), attaching paramagnetic groups to 2 0 -amino modified nucleotides or 4-thiouridines (Piton et al, 2007;Qin, Feigon, & Hubbell, 2005), and the use of paramagnetic phosphoramidites during RNA synthesis (Wunderlich et al, 2013).…”
Section: Spin Labeling Of Protein-rna Complexesmentioning
confidence: 99%
“…Several methods have been developed to attach a paramagnetic tag to nucleic acids (Keyes & Bobst, 2002;Nguyen & Qin, 2012;Qin & Dieckmann, 2004;Shelke & Sigurdsson, 2012): these include replacing structural Mg 2+ with paramagnetic Mn 2+ (Bonneau & Legault, 2014;Kisseleva, Khvorova, Westhof, & Schiemann, 2005), attaching paramagnetic groups to 2 0 -amino modified nucleotides or 4-thiouridines (Piton et al, 2007;Qin, Feigon, & Hubbell, 2005), and the use of paramagnetic phosphoramidites during RNA synthesis (Wunderlich et al, 2013). In the case of large RNAs, annealing and ligating short spin-labeled oligonucleotides to a larger RNA scaffold (Helmling et al, 2014), and enzymatically, using T7 RNA polymerase (Lebars et al, 2014) have been reported.…”
Section: Spin Labeling Of Protein-rna Complexesmentioning
confidence: 99%
“…The former strategy is usually applied in solid-state [26] or solution-state [27] synthesis of peptides and for oligonucleotides [15] and allows a broad variation of labeling chemistry [28]. In this scenario, one often aims for a rigid coupling of the label to the backbone of the macromolecule and for the least possible conformational ambiguity of the label.…”
Section: Labeling Strategy and Common Spin Labelsmentioning
confidence: 99%
“…A series of these novel, unique structures are shown in Figure 9. This work was then copied and extended by other groups, particularly the Seattle group (University of Washington) that also designed nucleotide analogues for probing DNA [14]. In all cases the syntheses were truly challenging, could only be carried out by very proficient organic chemists, and support the view of this author that synthetic organic chemistry is the rate-limiting step in many of these biophysical probe experiments.…”
Section: Nucleic Acid Analoguesmentioning
confidence: 89%